Plague and other flea-borne infections - Griffith, Kevin S. (Henry Stewart Talks, 2010)
Overview of fleas, Background and epidemiology of plague, Clinical aspects of plague, including manifestations, diagnostics, and treatment, Control and prevention of plague, Other flea-borne infections